Management kulturnega faktorja kot determinanta tujih neposrednih investicij - Vaupot, Zoran (Management, 2014)
The empirical research of determining factors concerning foreign direct investments (FDI) has started to grow in their importance since the 1980s of the previous century. The main reason for that was international growth of FDI volume. In the 1990s, we started to observe an integration of national culture's factor as an explanatory variable in models that try to explain changes concerning FDI. An overview of referential research shows that results, connected with a mentioned role of a national culture's factor are often contradictory. Taken it into account, we first try to analyze basic reasons of that fact. After that, some directions for improvements in methodological approach and areas of future research are proposed in order to better evaluate the role of national culture as determining factor of FDI.
Keywords: direktne investicije; ekonomska politika; tuje investicije